Optimizing the Performance of the Malang City Police Criminal Research Unit through Investigation Activities to Improve Online Fraud Cases Resolution (Indonesian Journal of Police Studies, 2024)
The current era of development has reached the era of revolution 5.0. The focus of the 5.0 revolution is how technology used to enhance the role of humans and optimize their abilities in the industrial environment. Along with that, crimes using cyber are also increasing, such as online fraud, which is rife in Malang City, East Java. The aim of carrying out this research is to optimize the performance of the Malang City Police Criminal Investigation Unit through investigative activities to increase the resolution of online fraud cases. The theories used in this research are the theory of organizational management elements, competency theory, and SWOT analysis theory as an analysis tool. The research conducted using descriptive-analytical methods and qualitative data analysis techniques through interviews, observation and document study. The results of the research show that the performance of the Malang City Police Criminal Investigation Unit in investigating criminal acts of online fraud is still not optimal, as evidenced by the absence of successful online fraud cases uncovered from 2020 to 2020. 2022. Based on the results of the analysis, several factors that influence investigative actions, such as the methods implemented are not in accordance with the regulation of the investigation of criminal acts and increase the competence of the Malang City Police Criminal Investigation Unit. Therefore, this research provides several suggestions in order to optimize the performance of the Malang City Police Criminal Investigation Unit in the process of investigating criminal cases of online fraud. It is hoped that the results of this research can be a reference for the police to improve the performance of the Malang City Police Criminal Investigation Unit in conducting investigations of criminal acts of online fraud.
Keywords: Kata kunci: Kinerja, Satreskrim, Polresta, Kota Malang, Kompetensi, Metode, Penyidikan